Comprehensive review of 2‐ethyl‐1‐hexanol as an indoor air pollutant. Issue 1 (21st January 2019) - Wakayama, Takanari; Ito, Yuki; Sakai, Kiyoshi; Miyake, Mio; Shibata, Eiji; Ohno, Hiroyuki; Kamijima, Michihiro
Abstract: Objectives: 2‐Ethyl‐1‐hexanol (2EH), a fragrance ingredient and a raw material for the production of plasticizer di(2‐ethylhexyl) phthalate, is responsible for sick building syndrome (SBS). This review aims to clarify the 2EH characteristics as an indoor air pollutant such as indoor air concentration, emission mechanism, toxicity, and clinical effects. Methods: Scientific publications in English that has been made available on PubMed as of June 2018 and ad hoc publications in regional languages were reviewed. Results: Inhalation exposure to 2EH caused mucous membrane irritation in the eyes, nose, and throat in experimental animals. Studies in human volunteers revealed an increase in olfactory irritation and eye discomfort. There has been increasing evidence of 2EH being present in indoor air in buildings. The primary sources of 2EH emissions are not building materials themselves, but instead the hydrolysis of plasticizers and flooring adhesives. In particular, compounds like di(2‐ethylhexyl) phthalate present in polyvinyl chloride flooring materials are hydrolyzed upon contact with alkaline moisture‐containing concrete floors. That being said, it may be observed that indoor concentrations of 2EH increased every year during summer. Conclusions: Unlike other volatile organic compounds that cause SBS, 2EH can be retained in indoor air for long durations, increasing the likelihood of causing undesirable health effects in building occupants exposed to it. As a precautionary measure, it is important to use flooring materials that do not emit 2EH by hydrolysis, or to dry concrete before covering with flooring materials.